The Impact Of Competitive Strategy And Intellectual Capital On SMEs Performance - Istianingsih; Robertus Suraji (Jurnal Manajemen, 2020)
This study aims to examine the impact of competitive strategies and intellectual capital on the performance of Small and Medium Enterprises (SMEs). The research sample is the owners of SMEs in the Banten region. The number of final samples obtained that can be included in the test is as many as 181 respondents of SME owners or 60.33% of the total intended respondents. The data analysis technique used is regression with structural equation models. The results showed that the Competitive Strategy proved to have a positive effect on the success of SMEs. The choice of the right competitive strategy can improve SME performance. Intellectual Capital Management is also proven to have a positive effect on the success of SMEs. The greater the Intellectual Capital, the more it will encourage SMEs to perform better. The implication of the results of this study is that in order to improve the competitiveness and success of SMEs, it is necessary to choose the right competitive strategy and manage their intellectual capital well.